PENGARUH MEKANISME CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Media Riset Akuntansi, 2022)
The purpose of this research to examine the effect of corporate governance mechanism and leverage of integrity financial statements. Corporate governance mechanism are proxy by variable independent commissioner size, audit committee size, institutional ownership, managerial ownership. The population in this study are companies listed on the Indonesia Stock Exchange in the period 2015-2018. The sampling technique in this study using purposive sampling method. The analytical method used multiple linear regression analysis method. The results show that the size of independent commissioners, the size of the audit committee, and managerial ownership influence the integrity of financial statements. Institutional ownership and leverage have no effect on the integrity of financial statements.